Spontaneous Nasal Septal Abscess: A Case Report - Bishow Tulachan; Roshan Acharya; Savita Aryal; Himal Poudel; Bishesh Regmi; Manoj Rimal; Bhuwal Agrahari (Journal of Universal College of Medical Sciences, 2025)
Spontaneous nasal septal abscess is a rare condition. It typically occurs following traumatic events preceded by septal hematoma. Prompt recognition and intervention are must to avoid further infective and cosmetic complications. Hence, it is considered as a rhinologic emergency. This is a case of 27 years female with complaints of nasal mass, swelling , pain and difﬁculty in breathing for 7 days. She was diagnosed as spontaneous nasoseptal abscess and surgical intervention made her symptoms free.